2015
DOI: 10.5455/msm.2015.27.442-446
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Medication Administration Errors and their Causes in Cardiac Critical Care Units in Iran

Abstract: Background and Objectives:The dangerous events caused by medication errors are one of the main challenges faced in critical care units. The present study was conducted to determine the frequency of intravenous medication administration errors and their causes in cardiac critical care units in Iran.Materials and Methods:The present descriptive study was conducted in the critical care units (CCUs and cardiac surgery intensive care units) of 12 teaching hospitals. Of the total of 240 nurses working in these depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(71 citation statements)
references
References 14 publications
2
58
0
10
Order By: Relevance
“…Many medication errors may be the result of cognitive errors in medical decision making, or skills‐based errors, or performance and knowledge deficits . The most commonly reported medication errors centred on miscalculated and mistaken doses, or missteps . Fifty‐three percent of the drug errors found by Kuo et al consisted of prescribing errors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many medication errors may be the result of cognitive errors in medical decision making, or skills‐based errors, or performance and knowledge deficits . The most commonly reported medication errors centred on miscalculated and mistaken doses, or missteps . Fifty‐three percent of the drug errors found by Kuo et al consisted of prescribing errors.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] The most commonly reported medication errors centred on miscalculated and mistaken doses, or missteps. 18,27,32,33,[35][36][37][38][39][40] Fifty-three percent of the drug errors The highest reported rate of communication errors was described as part of a cascade event analysis of anonymous error reports by Woolf et al 24 In an effort to identify various stages of mistakes and link chains of errors together, they found that 67% of errors reported by a group of family physicians could be attributed…”
Section: Discussionmentioning
confidence: 99%
“…If one of these standards was incorrect, it means unmoral result and defects in hail cells. [15,[31][32][33][34] The gathered data were analyzed using version 16 of SPSS Software. First, Kolmogorov-Smirnov method was used to test the normality of data and continuity and paired t-tests such as Tokay significant difference test were used to find mean with significant difference compare to other means, as well as compare the averages and means of PTA and DPOAEs of right and left ears in two control and experimental groups.…”
Section: Methodsmentioning
confidence: 99%
“…Velocidade de infusão errada 19,22,23,28,29,[31][32][33]36,[44][45][46]49,54,57 Infusão mais rápida ou mais lenta que o recomendado 15 5,7…”
unclassified
“…Paciente errado 1, 18,19,25,26,32,34,36,37,40,47,49,51,55 Administração de medicamento ao paciente errado 14 5,3 Monitoramento errado 19,26,32,36,38,43,49,53,[57][58][59]61 Medicamentos contraindicados, interações medicamento-medicamento, interação dietamedicamento, alergias documentadas, interação doença-medicamento, avaliação clínica 12 4,6…”
unclassified